Reliability and validity of the novel self-reported spine functional scale (SSFS) in healthy participants - Wei Li; Jie Ding; Xiujuan Hao; Wenjun Jiang; Hongqiang Song; Yanming Zhang; Yan Tan (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Objectives To develop the novel self-reported spine functional scale (SSFS) and conduct reliability and validity analysis, so that the public can better understand their own spine function in a more simple and scientific way, so as to effectively prevent spinal disorders and improve the quality of life through targeted rehabilitation therapeutic measures. Methods This study was approved by an institutional review board, and all subjects gave informed consent to participate. Results (1) Using Spearman correlation analysis to evaluate the content validity, each item was significantly correlated with the total score, and the project design was reasonable. The exploratory factor analysis method is used to evaluate the structural validity of the scale, and the standing position and the lying position of the posture evaluation can be attributed to the factor 2, which is called posture evaluation: the cervical flexor strength, the flat support, the prone back, and the supine knee. The back arch of the wall and the angel on the wall is attributed to factor 1, called the overall spine function test, and the cumulative contribution rate of the two factors was 46.057%. Confirmatory factor analysis showed that the two-factor model fits well (χ 2/df = 2.440, RMSEA = 0.04 < 0.05, GFI = 0.945, AGFI = 0.920, CFI = 0.967, IFI = 0.967, TLI = 0.951, GFI, AGFI, CFI, IFI, and TLI are > 0.90) and the validity is ideal. (2) The test-retest reliability shows that the test-retest reliability of each entry, each dimension, and the total score is greater than 0.5, and the test-retest reliability is high. The Cronbach α coefficient was used to evaluate the overall internal consistency of the scale, α > 0.70, indicating that the scale has high reliability. After deleting each item one by one, the α coefficient is 0.692–0.717, and there is no significant increase. (3) Sex and occupation did not affect the level of spinal function (P > 0.05), and there was interaction. Different BMI levels significantly affected the score of spinal function (P < 0.05). The rate of spinal dysfunction in overweight and obese subjects was significantly higher than the normal group; the overall score of spinal function was worse than the normal group. Discussion The reliability and validity analyses of this study verified the reliability and scientificity of SSFS in the young healthy population. Body weight had a significant influence on SSFS score, and the performance levels were different for the two sexes. Conclusion The novel Self-Reported Spine Functional Scale (SSFS) has high reliability and validity and is applicable to the self-assessment and maintenance of spinal health and the prevention of related spinal disorders in the young healthy population. Body weight has a significant influence on the SSFS score in healthy young people. Overweight and obese males were found to be more likely to have spinal dysfunction, while underweight males displayed poor cervical flexor muscle strength. Underweight females were found to have better overall spinal function and stronger cervical flexor muscle strength.